KEBIJAKAN PENANGANAN PELAYANAN KESEHATAN DI MASA PANDEMI COVID-19 - Chumaida, Zahry Vandawati; Ariadi S, Bambang Sugeng; Raden Roro, Fiska Silvia (Lex Journal: Kajian Hukum & Keadilan, 2021)
The Covid-19 pandemic in Indonesia has occurred for 2 years and has become a difficult task for health services. People who are infected, with the number of infections in Indonesia continuing to soar. This condition requires health service facilities and health workers to extra work to provide treatment for Covid-19 patients as a top priority. Healthcare facilities are starting to be selective in providing health services. The formulation of the problem raised is the problem with health services for the community and how the role of BPJS Health and the government in handling health services. The research method used is normative juridical, namely by analyzing the laws and regulations in force in Indonesia, using a conceptual approach, and legislation. The conclusion of this research is rules and regulations are needed to deal with cases, namely the Regulation of the Minister of Health of the Republic of Indonesia Number 19 of 2021 concerning the Second Amendment to the Regulation of the Minister of Health Number 10 of 2021 concerning the Implementation of Vaccination in the Context of Combating the Pandemic. Keywords: Policy, health services, Covid-19 pandemic